2016
DOI: 10.1128/aem.00643-16
|View full text |Cite
|
Sign up to set email alerts
|

Shape Changes and Interaction Mechanism of Escherichia coli Cells Treated with Sericin and Use of a Sericin-Based Hydrogel for Wound Healing

Abstract: To verify the interaction mechanism between sericin and Escherichia coli, especially the morphological and structural changes in the bacterial cells, the antimicrobial activity of sericin against E. coli as a model for Gram-negative bacteria was investigated. The antibacterial activity of sericin on E. coli and the interaction mechanism were investigated in this study by analyzing the growth, integrity, and morphology of the bacterial cells following treatment with sericin. The changes in morphology and cellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 22 publications
2
34
0
Order By: Relevance
“…4 ) which consequently could impair the cell membrane integrity leading to cell death 38 . The membrane defects caused by SMs resembles to those caused by already known membrane acting antibiotics such as polymixins (SM4-SM6) 37 , daptomycin (SM2, SM3, SM7, and SM11) 38 , ampicillin/cephalexin (SM1, SM8-SM10) 25 , 40 , and several other antimicrobial peptides 32 , 42 – 47 . Polymixins disrupt the outer membrane integrity of Gram negative bacteria by forming the blebs on the surface of the bacterium 31 .…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…4 ) which consequently could impair the cell membrane integrity leading to cell death 38 . The membrane defects caused by SMs resembles to those caused by already known membrane acting antibiotics such as polymixins (SM4-SM6) 37 , daptomycin (SM2, SM3, SM7, and SM11) 38 , ampicillin/cephalexin (SM1, SM8-SM10) 25 , 40 , and several other antimicrobial peptides 32 , 42 – 47 . Polymixins disrupt the outer membrane integrity of Gram negative bacteria by forming the blebs on the surface of the bacterium 31 .…”
Section: Discussionmentioning
confidence: 93%
“…SEM images suggest that SMs treatment produced membrane wrinkling, blebbing/vesicle-like structures, and pores (Fig. 4 ) which are the characteristics morphology induced by membranes acting antibiotics and several other antimicrobial agents 42 – 47 . DMSO treated APEC bacteria showed very few wrinkled smooth surfaced cells measuring 1–2 µM (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon 6 h of treatment with the peptide UTNGt21O, a dose response effect was observed with larger shaped spheroplasts having thicker and deformed membranes at 1X ( Figure 7 B) and filamentous cells, visibly notched in the outer and inner membrane, heterogeneous electron density cytoplasm and larger periplasmic space at the concentrations of 1.5× and 2× MIC ( Figure 7 C,D). Early studies of E. coli treated with different antibiotics indicated that the filamentation probably occurs if DNA synthesis is inhibited [ 38 , 39 ]. A bacteriocin produced by W. confusa A3 isolated from milk was found to induce damage in the cell membrane of Bacillus cereus , a Gram-positive bacterium, as shown by TEM analysis [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…B) for IWJ001/pDXW‐8‐ cysK cells. The elongated and inflated IWJ001/pDXW‐8‐ cysK cells may affect the cell envelope and further affect the membrane permeability . The increased membrane permeability can benefit the uptake of glucose and the secretion of l ‐isoleucine .…”
Section: Disscusionmentioning
confidence: 99%